Medicinal plants with wound healing potential (Bangladesh Journal of Pharmacology, 2018)
Wound occurs due to disruption of soft tissues that results from injury. Recently many medicinal plants have been demonstrated for wound healing potential through in vivo and in vitro preclinical models and their mechanisms of wound healing has also been reported. Medicinal plants have been reported to show wound healing potential via angiogenesis, activation of NF-κB, favoring pro-inflammatory cytokines, increased expression of inducible nitric oxide synthase (iNOS) and alpha 1 type 1 collagen, and anti-oxidant activity. Thus, in this review, an attempt was made to give an insight into the recently reported medicinal plants with wound healing mechanisms which could be beneficial in therapeutic practice and development of new wound healing drugs for human use.